Determination of Tax Aggressiveness in the Mining Sector in Indonesia - Safitri, Devi (Accounting Analysis Journal, 2024)
Purpose: The self assessment system is one of the tax collecting mechanisms in Indonesia. This collecting method gives taxpayers to calculate their own tax liability each year in compliance with current tax rules and regulations (Resmi, 2019). This allows companies to calculate their taxable revenue as low as feasible, allowing them to be more aggressive in lowering the tax burden paid in order to maintain firm profitability. This research aims to substantiate the hypothesized influences on tax aggressiveness. Capital intensity, profitability, and firm size are the independent variables under consideration. Method: The mining companies that were officially registered on the Indonesia Stock Exchange from 2017 to 2021 constitute the study population. The rationale behind the author's selection of a mining company is the suspicion that engineering practices to relocate income globally to low-tax countries and substantial costs to high-tax countries are still prevalent. The sampling procedure utilized is purposive sampling, in which samples are selected in accordance with predetermined criteria that the researchers have established. A total of 95 samples were acquired from 19 enterprises that met the specified criteria over the course of five years. In this investigation, multiple regression analysis was conducted. Findings: It was discovered that tax aggressiveness was negatively correlated with profitability. Inversely proportional to capital intensity is tax aggressiveness. As it contradicts the developed hypothesis, this hypothesis is refuted on account of the positive correlation between company size and tax aggressiveness. Novelty: Utilizing an agency theory framework, this study contributes to the literature on tax aggressiveness in mining companies listed on the Indonesia Stock Exchange, which is influenced by capital intensity, profitability, and company size. It was demonstrated by the study that capital intensity and profitability can influence tax aggressiveness